1999
DOI: 10.1109/42.802754
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic electrical impedance tomographic measurements during volume controlled ventilation-effects of tidal volume and positive end-expiratory pressure

Abstract: The aim of the study was to analyze thoracic electrical impedance tomographic (EIT) measurements accomplished under conditions comparable with clinical situations during artificial ventilation. Multiple EIT measurements were performed in pigs in three transverse thoracic planes during the volume controlled mode of mechanical ventilation at various tidal volumes (V(T)) and positive end-expiratory pressures (PEEP). The protocol comprised following ventilatory patterns: 1) V(T)(400, 500, 600, 700 ml) was varied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 25 publications
5
97
0
Order By: Relevance
“…The lighter an area, the larger the local end-expiratory-to-end-inspiratory relative impedance change. These images were previously termed by us "functional EIT images of regional lung ventilation" [6,8]. They characterise the magnitude of local ventilation in the chest crosssection and visualise the ventilated lung regions.…”
Section: Off-line Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The lighter an area, the larger the local end-expiratory-to-end-inspiratory relative impedance change. These images were previously termed by us "functional EIT images of regional lung ventilation" [6,8]. They characterise the magnitude of local ventilation in the chest crosssection and visualise the ventilated lung regions.…”
Section: Off-line Data Analysismentioning
confidence: 99%
“…Thanks to the excellent time resolution EIT is able to determine not only the local magnitude of lung ventilation and local resting volume (e.g. [6,7]) but also the dynamics of local filling and emptying of lung units [8]. In view of these EIT features in monitoring local lung function, it is expected that EIT may be useful in the assessment of the efficacy of therapeutic interventions, including mechanical ventilation, and in the prediction of the progress of acute and chronic lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of regional changes in lung volume by this method is based on the fact that local variations in gas volume modify the electrical properties of the lung tissue which EIT is able to determine. Our previous studies have demonstrated the ability of EIT to assess regional lung function under multiple experimental and clinical conditions [2,3,4,5,6]. In critically ill infants, EIT may be beneficial not only by providing the otherwise inaccessible quasi-continuous information on regional lung ventilation directly at the bedside, but also by reducing the number of thoracic X-ray examinations.…”
mentioning
confidence: 99%
“…The corresponding regional differences in impedance may be imaged as a functional scan and reflect the change in regional lung volumes [32,33]. In a clinical setting, this may be observed when the ventilator settings are modified, e.g., when regional lung aeration changes as a result of PEEP adjustment [30,34] (see also Fig. 3, the lower scan).…”
Section: Functional Eit Imagingmentioning
confidence: 99%